Promoting the Engaging Programs of the Pemuda Indonesia Mosque as a Religious Destination - Ainin Ainiya Nurriffah; Siti Kris Fitriana Wahyu Lestari; Putri Aqila Nadya (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2026)
This research aims to analyse the impact of promotions on the effectiveness of enganging programs organised by the Indonesian Youth Mosque. In this context, effective promotion can be a key factor in increasing community participation, especially among youth, in various religious and social activities. The Indonesian Youth Mosque acts as an activity centre that not only focuses on spiritual aspects but also on empowering youth through relevant and innovative programs. This research uses a descriptive qualitative approach method with in-depth interviews, participatory observation and documentation as data collection techniques. The research results show that a promotion that is right on target and supported by social media is able to attract the interest of young people to be actively involved in mosque activities. These findings provide important implications for mosque managers in designing more effective promotional strategies.